Developing Learning Motivation of Elementary School Students Through Discovery Learning Model - Rahman, Alma Firriyal; Husna, Nida’Ul; Rizqiani, Hanifah; Rachmawati, Umi (Prosiding University Research Colloquium, 2021)
The purpose of this study is to find out how the influence of the use of discovery learningmodel as a means of improving the learning motivation and learning outcomes of grade VIstudents in 03/20 Nambangan, North Rejowinangun, Central Magelang district, MagelangCity in the era of the covid-19 pandemic. This study uses class action research (PTK). Aclass were selected in this study. Data collection are gathered from the students’ reportbook and postest through the use of discovery learning model. Based on the results of dataanalysis in cycle one with an average of 50 before the treatment while in cycle II there isan average increase of 100 after the treatment of the discovery learning model. It can beconcluded that discovery learning model can increase students' learning motivation andlearning outcomes